Gallbladder Mixed Neuroendocrine-Non-Neuroendocrine Neoplasms: A Case Report - Aboulfeth, EL Mehdi; EL Kaoui, Hakim; Tbouda, Mohammed; Bouzroud, Mohamed; Moujahid, Mountassir; Bounaim, Ahmed (International Journal of Innovative Research in Medical Science, 2020)
The gallbladder Mixed neuroendocrine-non-neuroendocrine neoplasms (MiNEN) are extremely rare. The association of at least two components including one neuroendocrine tumor, and a non-neuroendocrine one defines MiNEN. We are reporting a case of 50-year-old woman referred to our department for management of a gallbladder tumor suspected on imaging. She undergone a cholecystectomy enlarged to the vesicular bed according to Gleen and hepatoduodenal lymphadenectomy. The histological examination conclude on MiNEN of the gallbladder; and the patient received adjuvant chemotherapy and she shows no sign of recurrence at 6 months.